Reappraising ‘the good death’ for populations in the age of ageing - Pollock, Kristian; Seymour, Jane (Oxford University Press, 2018)
This is the second in an occasional series of paired commentaries in Age and Ageing, the Journal of the British Geriatrics Society and the Journal of the American Geriatrics Society (JAGS). The aim is to address issues of current significance and to foster dialogue and increased understanding between academics and clinicians working in comparative international settings. Both commentaries address the urgent need to improve palliative care for older people, with a critique of some stereotypes surrounding palliative care and the ‘good death’. The companion commentary, published in JAGS, was written by Alexander Smith and Vyjeyanthi Periyakoil, and is grounded in their experience as academic clinicians (Smith AK, Periyakoil V. Should we bury ‘The Good Death’? Journal of the American Geriatrics Society 2018; in press). In the present paper, we offer a perspective on the outcome and wider consequences of misalignment between current UK policy and aspirations for end of life care in relation to epidemiological trends and patient experience of death and dying.